India’s Urban Growth in Recent Times: Need for Sustainable Urban Development Strategies - Mahadeva, M. (The journal of contemporary issues in business and government, 2021)
India’s urbanisation process can be characterised as divisive and uneven, owing to lack of sustainable public strategies benefitting to all sizes of cities and towns in the country. The urbanisation is highly inclined to major urban centres, including the state capitals and is conspicuously uneven, due to improper development of public infrastructure and public services, especially in the small and medium towns. The urbanisation process has largely driven by the economic considerations like increased employment opportunities, higher income earnings and other social benefits and comforts than the human settlement challenges. Having been promoted and nurtured the main urban centres, the urbanisation process has not only divided the settlements over the decades but also displaced smallest towns in the recent years. The small and medium towns being the settlements of low-income groups and the immediate tiny service centres, continuing to suffer without the basic socio-economic infrastructure. Realisation of the urban outcomes although has led to the public intervention in the late 80s but its effectiveness to ensure sustainable urban development is far from satisfaction. This is largely due to mandatory participation in expenditure sharing by the states and due to lack of political will for the sub- regional development. As a result, the impact of IDSMT is not widespread across the country but limited to selected major states, which have had the capacity to share the public expenditure and exhibited the political will. Above all, complete abandonment of the ongoing strategic development without adequate alternative design is a serious setback to decent and orderly urban life at the hitherto neglected small and medium towns. The emergent urban challenges have been discussed in greater details and this paper offers a sustainable policy imperative, as contributions to the effective public intervention, to achieve the desired goals of the inclusive urbanisation and orderly urban life in the country.